Penerapan Teknologi Operasional Penggunaan Mesin Penarik Kulit Kambing UKM ‘Mak Ngat’ Dipasar Rasamala Perumahan Srondol Wetan Kecamatan Bayumanik Kota Semarang - Trio Setiyawan; Riles WM; Sugeng Irianto; Timotius Anggit; Nurhidayati Nurhidayati; Hery Tristijanto; Avicenna An-Nizami; Iman Mujiarto; Yuris Bahadur Wirawan; Elfrida Rizky Riadini; Ahmad Mamba'udin (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The partners for this community service activity are UMKM which are engaged in goat slaughtering. One of the problems faced is that the process of removing goat skin is still manual, that is, it still uses human labor, where using human power for the goat skinning process requires less efficient time. Therefore, these UMKM really need a touch of technology related to the goat skin removal method to overcome the problems of UMKM engaged in the business of slaughtering goats and selling goat meat. Therefore, in community service activities, goat skin pulling machines will be handed over to partner entrepreneurs, namely MSMEs. Mak Ngat at the Rasmala market in the Srondol Wetan housing complex, Banyumanik sub-district, Semarang city. Impact After using a goat skin pulling machine for Mak'Ngat UMKM, the goat skinning process is more economical, namely when done manually it can skin 12 goats in one hour, but when done using a machine, 12 goats can be done in 15 minutes and this number has increased drastically